Cost-Effectiveness of a Low-Cost, Hospital-Based Primary Care Clinic. (13th November 2014) - Agee, Mark D.; Gates, Zane; Reilly, Patrick
This study assesses the cost-effectiveness of an insurance administration-free, hospital-based clinic designed to provide a full array of primary care services to low-income individuals at little or no cost. In addition to low/no-cost visits, individuals have the option to purchase a low-cost health insurance plan similar to any traditional health plan (eg, prescriptions, primary care, specialty care, durable medical equipment, radiology, laboratory test results). We used 3 years of data (2009-2012) on emergency department (ED) visits and inpatient hospital admissions from clinic patients and patients at the community's 2 largest private physician groups to assess the cost-effectiveness of the hospital-based clinic in terms of ED and inpatient admission costs avoided and financial sustainability of the low-cost insurance plan. Estimated annual savings in hospital inpatient and ED costs were approximately 1.4 million. Insurance plan data indicated sound fiscal sustainability with modest provider reimbursement growth and zero annual premium growth.